Cracking of jujube fruits is associated with differential expression of metabolic genes. Issue 9 (29th July 2020) - Liu, Yaling; Zhang, Pengfei; Geng, Yaping; Xie, Xiaodong; Wen, Pengfei
Abstract : Cracks in the skin of jujube fruit reduce freshness and quality; thus, greater understanding of the molecular mechanism that underlies cracking is required to improve fruit production. In this study, we profiled genes that are differentially expressed between cracked and normal jujube fruits through RNA sequencing (RNA‐seq). We selectively confirmed differentially expressed genes (DEGs) using quantitative RT‐PCR. Among 1036 DEGs, 785 genes were up‐regulated and 251 genes were down‐regulated in cracked jujube fruits. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis indicated that some of these DEGs encode proteins involved in metabolic processes (including growth hormone and surface wax production) in cracked jujube fruits. In summary, we have identified differentially expressed metabolic genes between cracked and normal jujube fruits, which may serve as the basis for further studies of fruit quality control. Abstract : Here, we identified differentially expressed genes (DEGs) between cracked and normal jujube fruits, of which 785 DEGs were up‐regulated and 251 DEGs were down‐regulated. Several DEGs encode proteins with roles in metabolic processes, including growth hormones and surface wax production.